A new flavanone and other flavonoids from green perilla leaf extract inhibit nitric oxide production in interleukin 1β-treated hepatocytes. Issue 1 (2nd January 2015) - Nakajima, Ayaka; Yamamoto, Yuka; Yoshinaka, Nao; Namba, Mayuri; Matsuo, Hirotaka; Okuyama, Tetsuya; Yoshigai, Emi; Okumura, Tadayoshi; Nishizawa, Mikio; Ikeya, Yukinobu
Abstract: A new flavanone, shisoflavanone A (1), and several flavonoids were purified from the ethyl acetate-soluble fraction of green perilla leaves ( Perilla frutescens Britton var. crispa form viridis ), and their structures were identified. Shisoflavanone A was elucidated as 8-hydroxy-6, 7-dimethoxyflavanone based on its spectral data. Other constituents of the ethyl acetate-soluble fraction, i.e. 5, 8-dihydroxy-7-methoxyflavanone (2), negletein (5, 6-dihydroxy-7-methoxyflavone) (3), luteolin (4), apigenin (5), esculetin (6), and protocatechuic acid (7), were identified. This is the first time that constituents 2, 3, and 6 have been found in green perilla . Shisoflavanone A and the other constituents (except 7) significantly inhibited nitric oxide production in interleukin 1β-stimulated rat hepatocytes, which have been used to monitor the anti-inflammatory effects of herbal constituents. The present findings suggest that these constituents, including shisoflavanone A, may be involved in the anti-inflammatory effects of green perilla leaves. Graphical abstract: : A new flavanone, shisoflavanone A and other flavonoids from green perilla leaf extract inhibit nitric oxide production in interleukin 1β-treated hepatocytes